Cross-Sectional Survey of Prophylactic and Metaphylactic Antimicrobial Use in Layer Poultry Farming in Cameroon: A Quantitative Pilot Study - Mouiche, Mohamed Moctar Mouliom; Wouembe, Frank Dupleix Khalen; Mpouam, Serge Eugene; Moffo, Frédéric; Djuntu, Michael; Toukam, Claude Michel Wombou; Kameni, Jean Marc Feussom; Okah-Nnane, Ndode Herman; Awah-Ndukum, Julius (Frontiers in Veterinary Science, 2022)
An evaluation of the patterns of antimicrobial use in livestock can help understand the increasing level of antimicrobial resistance worldwide. This study aimed at evaluating antimicrobial usage in modern layer poultry farms in the West Region of Cameroon. In this light, 70 layer poultry farms and 4 veterinary pharmacies were surveyed. Data on antimicrobial use were collected through interviews using a quantitative-frequency questionnaire and consultation of medical records. The four veterinary pharmacies sold a total of 2.8 tons of antimicrobials (active ingredients) during 2011. At the level of farms, 297 kg of antimicrobials (active ingredients) were used in the 50 layer poultry farms surveyed. Tetracycline, sulfonamides, quinolones, and β-lactams (aminopenicillins) were the most sold and used drugs in layer farms. As for treatment indication, metaphylactic (58.1%) and prophylactic (41.9%) treatments were the most observed practices, and nearly all (99%) treatments were administered per os as remedies to respiratory (33.4%) and digestive (24.7%) tract symptoms. Overall, 78.2% of antimicrobials sold in pharmacies and 67.3% used in the farms belonged to the class of critically important antimicrobials of the WHO categorization of antimicrobials according to their importance to human medicine. Doxycycline, sulfonamide, ampicillin, and streptomycin, which have been banned for layer poultry in the production of eggs for human consumption, were still used in Cameroon. The treatment incidences based on the used daily dose (TIUDD) and animal daily dose (TIADD) were 11.59 and 10.45, respectively. In regard to dosage correctness based on the UDD/ADD ratio, aminoglycosides (100%), macrolides (90.6%), and tetracyclines (74.5%) were the most underdosed, while trimethoprim sulfonamides (45.8%) and β-lactams (35.7%) were overdosed. This study highlights an irrational antimicrobial usage in layer poultry farms. Regulation of the use of antimicrobials and the education of farmers on adequate antimicrobial use are essential to preserve the effectiveness of drugs in both humans and animals.